The Impact of Service Quality, Customer Satisfaction, and Trust on Customer Loyalty among BRILink Agents in North Sumatra - Firmansyah, Fandi; Sugiat, Maria; Yunita, Irni (Publisher Cv. Inara, 2023)
Abstract. The shift of business into the digital era demands the banking industry to innovate in serving customers. One of the innovations by PT. Bank Rakyat Indonesia is the e-channel service named Brilink, which is spread across all regions. Local entrepreneurs are appointed as Brilink agents with the aim of providing banking services to individuals who are not yet served by banks, both unbanked and unbankable as stipulated in Article 16 of POJK No. 19/POJK.03/2014. Public distrust towards Brilink agents is attributed to the quality of service provided by these agents, which does not align with BRI's service standards, particularly in utilizing the Brilink application. Therefore, this research aims to examine the influence of the service quality, customer satisfaction, and trust variables on customer loyalty at Brilink agents in North Sumatra, Indonesia. This study employs a quantitative approach with a sample size of 400 respondent customers of Brilink agents. The research offers insights into the role of Brilink agents in marketing products, thus facilitating their understanding and utilization by customers. Furthermore, it holds social benefits in enhancing financial literacy and inclusion among the population in North Sumatra, ultimately contributing to welfare improvement and economic growth. Keywords: service quality, customer satisfaction, trust, customer loyalty.